Skillful Engagement with Wicked Issues A Framework for Analysing the Meaning-making Structures of Societal Change Agents. - Jordan, Thomas (Integral Review: A Transdisciplinary & Transcultural Journal for New Thought, Research, & Praxis, 2011)
The argument underlying this article is that innovative and skillful change strategies are needed in order to handle a range of complex and difficult societal issues. For many of these so-called wicked issues, conventional institutions and policies have performed rather poorly. It can be reasonably argued that societal change agents play a crucial role in catalysing developmental processes regarding our societies' problemsolving strategies and organizational forms. The purpose of this article is to contribute to a deeper understanding of the different ways societal change agents engage wicked issues by developing a conceptual framework for analysing the meaning-making patterns of change agents. The framework integrates relevant concepts and models from the field of adult development with a specific focus on the role of awareness in five domains: task complexity, context, stakeholders, self, and perspectives. The framework is expected to be useful in analysing and explaining the variability in how societal change agents construct visions, goals, strategies, and courses of action, as well as in analysing patterns of effectiveness and success in initiatives that engage complex societal issues. Knowledge gained from such studies can (presumably) be used for designing more effective forms of scaffolding individual competence development as well as collective problem-solving and strategy development processes.